Stunting Interventions in Developing Countries: Literature Review - Fardila elba; Hassan, Hafizah Che; Umar, Nur Syazana; Hilmanto, Dany (International Journal of Health Sciences, 2023)
Stunting is a condition in which a toddler is shorter than their own age. This condition is defined as having a body length or height that is greater than the - 2 SD median of WHO child development criteria. Childhood stunting can have an effect on growth and development. Growth is not ideal, and developmental hurdles arise from birth, resulting in low educational achievement later in life. To reduce the risk of stunting, it is essential to identify and implement appropriate and optimal action as soon as possible in order to avoid or minimize lasting negative effects on children's growth and development. It aims at determining the way in which stunt interventions take place in a few developing countries. The research plan utilized may be a Writing Survey utilizing the Prisma strategy, which depicts the comes about of hindering intercessions in creating countries. Fifteen articles met the incorporation criteria. Most come about of the article talks about education intervention and multi-micronutrients. In Indonesia, four articles show results with a significant impact on the p-value. and;0.05, 3 articles had no effect in Cambodia, 2 articles showed significant results in India, and 3 influential articles in Ethiopia with p-value and;0.05, impact had a p-value of <0.05.